Performance comparison of sorghum varieties treated with NP and NPSZn fertilizers in the Raya Valley, Northern Ethiopia - Egziabher, Yemane G.; Gebrekorkos, Gebremeskel; Tsehaye, Yemane; Giday, Kidane; Mengistu, Dejene K. (Mekelle University, 2024)
The productivity of sorghum, an important staple food crop in Ethiopia, has been constrained by environmental stresses and declining soil fertility, and addressing these constraints improves the productivity of sorghum. A field experiment was conducted in Raya Valley to evaluate the responses of eight sorghum varieties to NPSZn and NP fertilizers and to select the varieties that combine desirable traits. The field experiment was laid out in RCBD in three replications. The varieties showed significant (p<0.001) variations for phenological, agronomic, and physiological traits. Meko and Melkam were the early maturing varieties with different yielding potential. Melkam was the second highest (4808 kg ha-1) yielding variety after Dagnew. Melkam has combined desirable traits, earliness, and high yield, for production in semi-arid drought-prone areas like the Raya valley. The local sorghum varieties outperformed Meko in most traits, which shows their potential use in breeding and production systems. NPSZn and NP fertilizers did not affect the studied traits differently but differed significantly from the zero treatment. The variety × fertilizer interaction effect was significant on most traits except PW, TGW, and GY. NPSZn treatment has increased biomass yield by 18.4% and 8.6% over NP in Gombilu and Dagnew, respectively. High LA and LAI were recorded from the high-yielding varieties, Dagnew and Melkam, and vice versa for low-yielding varieties. It can be concluded that working for varietal selection could be more rewarding than switching the application of NP to NPSZn fertilizer type in the Raya Valley to enhance sorghum production and productivity. The 100 kg ha-1 NPSZn blend recommendation, however, makes a 50% fertilizer price discount. Hence, Melkam from improved and Dagnew from the local varieties had better performance and can be preferably cultivated by farming communities.